Abnormal error-related antisaccade activation in premanifest and early manifest Huntington disease - Rupp, J. (2011)
OBJECTIVE: Individuals with the trinucleotide CAG expansion (CAG+) that causes Huntington disease (HD) have impaired performance on antisaccade (AS) tasks that require directing gaze in the mirror opposite direction of visual targets. This study aimed to identify the neural substrates underlying altered antisaccadic performance. METHOD: Three groups of participants were recruited: 1) Imminent and early manifest HD (early HD, n=8); 2) premanifest (presymptomatic) CAG+ (preHD, n=10); and 3) CAG unexpanded (CAG−) controls (n=12). All participants completed a uniform study visit that included a neurological evaluation, neuropsychological battery, molecular testing, and functional magnetic resonance imaging during an AS task. The blood oxygenation level dependent (BOLD) response was obtained during saccade preparation and saccade execution for both correct and incorrect responses using regression analysis. RESULTS: Significant group differences in BOLD response were observed when comparing incorrect AS to correct AS execution. Specifically, as the percentage of incorrect AS increased, BOLD responses in the CAG− group decreased progressively in a well-documented reward detection network that includes the pre-supplementary motor area and dorsal anterior cingulate cortex. In contrast, AS errors in the preHD and early HD groups lacked this relationship with BOLD signal in the error detection network, and BOLD responses to AS errors were smaller in the two CAG+ groups as compared with the CAG− group. CONCLUSIONS: These results are the first to suggest that abnormalities in an error-related response network may underlie early changes in AS eye movements in premanifest and early manifest HD.